Mindfulness-Based Stress Reduction for Parents of Young Children with Developmental Delays: Implications for Parental Mental Health and Child Behavior Problems - Neece, Cameron L. (Journal of applied research in intellectual disabilities, 2014)
Background Parents of children with developmental delays (DD) typically report elevated levels of parental stress compared with parents of typically developing children. Children with DD are also at high risk for exhibiting significant behaviour problems. Parental stress has been shown to impact the development of these behaviour problems; however, it is rarely addressed in interventions aimed at reducing child behaviour problems. The current study examined the efficacy of mindfulness‐based stress reduction (MBSR) for parents of children with DD by investigating whether this intervention is effective in reducing parenting stress and whether decreases in parenting stress lead to reductions in behaviour problems among children with DD. Materials and methods Forty six parents of children with DD were randomly assigned to an immediate treatment or wait list‐control group. Participants completed questionnaires assessing parental stress and child behaviour problems at intake and at a second assessment, which took place after only the immediate treatment group had received the MBSR. Results Parents who participated in MBSR reported significantly less stress and depression as well as greater life satisfaction compared with wait list‐control parents. Regarding child outcomes, children whose parents participated in MBSR were reported to have fewer behaviour problems following the intervention, specifically in the areas of attention problems and ADHD symptomatology. Discussion Results indicated that MBSR may be an effective intervention for ameliorating parental stress and mental health problems among parents of children with DD. Additionally, these benefits may ‘spill over’ and improve behaviour challenges among these children.